A role of tumor susceptibility gene 101 (TSG101) in innate immune response of crayfish Procambarus clarkii. (November 2017) - Sun, Yu-Xuan; Tang, Lin; Gao, Jin; Feng, Yuan-Yuan; Peng, Tao; Yu, Ying-Ying; Yang, Liang-Li; Sun, Yu; Zhu, Bao-Jian
Abstract: Tumor susceptibility gene 101 (TSG101) is a multi-functional gene involved in cell growth and proliferation in vertebrates. However, its role in the innate immune response of crustaceans remains unclear. Here, a TSG101 gene was identified in crayfish Procambarus clarkii with an open reading frame of 1320 bp that encoded a predicted 48.3-kDa protein highly homologous to those in other invertebrates. TSG101 mRNA was highly expressed in stomach and hepatopancreas, and its expression was induced significantly in different tissues (hemocytes, gills and intestine) by lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (poly I: C) with various expression patterns. Recombinant TSG101 protein was expressed in Escherichia coli, and a possible protein-protein interaction between TSG101 and hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs) was explored by far-western blotting. RNA interference of TSG101 affected the gene expression of members of the Toll pathway. These results suggest that TSG101 is involved in the innate immune responses of P. clarkii . Highlights: A tumor susceptibility gene TSG101 was first characterized from P. clarkii. The expression patterns of TSG101 under immune challenges were investigated. TSG101 RNAi influenced the expression of immune-related genes in Toll pathway. The interaction between TSG101 protein and Hrs protein was explored.